Detection of typhoid carriers by duodenal fluid culture in a tertiary care hospital, Karachi: a cross-sectional study - Sonia Qureshi; Mohammad Tahir Yousafzai; Shafquat Rozi; Shahida Qureshi; Aneeta Hotwani; Kamran Sadiq; Om Parkash; Abdul Momin Kazi; Furqan Kabir; Hadi Usmani; Farah Naz Qamar (Journal of the Pakistan Medical Association, 2021)
Published in August 2021.